Teaching practicum for primary teacher education students during the COVID-19 pandemic - Irena Hergan; Mojca Pečar (Universidad de Deusto, 2022)
The paper presents results of the research on pre-service student teachers' assessment of the usefulness of their distance teaching practicum during COVID-19 for their professional development. The sample included 238 student teachers in the 3rd and 4th years of the bachelor's degree programme as well as those in the master's degree programme at the Faculty of Education, University of Ljubljana. The students answered the online questionnaire after completing their teaching practicum in spring 2020. The results show that the majority of the students spent more than half of their time during the teaching practicum preparing various teaching materials for the pupils. About a fifth of the students provided individual help to pupils, while only a small share of them conducted their lessons via videoconferencing. The 3rd year students rated the usefulness of preparing teaching materials and the overall usefulness of the distance teaching practicum statistically significantly lower than their senior colleagues. Whether the teaching practicum is implemented in an online environment or "live", it is important to insist that student teachers assist their pupils in all phases of the teaching process and adapt it to their individual characteristics and needs to the greatest extent possible. Received: 3 December 2021 Accepted: 7 November 2022